Fiscal Decentralization and Local Financial Autonomy: A Bibliometric Review of Global Research Trends - Edem Lekettey; Vanessa Gaffar; Juliana Juliana; Nugraha Nugraha (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This paper examines the prominent themes of research, intellectual connections, gaps in scholarship on the subject of local government financial autonomy in the world literature through bibliometric tools. Method: Bibliometric analysis of 626 publications in the Scopus index (2000-2025) with the VOSviewer software was performed to chart the occurrence of two or more keywords, thematic networks, citation network, and co-authorship network. The discussion follows the historical developments of the use of fiscal decentralization and local financial autonomy in terms of time, geography, and scientific fields. Findings: Nine thematic clusters were chosen that are reflections of intellectual organization of the subject-area, encompassing such areas as fiscal decentralization, urbanization, intergovernmental transfers, environmental regulation and digital governance. The research output has increased considerably since 2005 where the focus has shifted in terms of fiscal efficiency discussions to sustainability and technology-based governance issues. The best collaboration networks are between China and Europe and low involvement of Africa and Latin Americans. The temporal analysis shows that the financial crisis globally and the COVID-19 outbreak has fueled the study of fiscal resilience and adaptive financial management research. Implications: This study shows the need for developing countries to deploy digital tools and enhance their intergovernmental transfer design, as well as capacity-building strategies that are often used by developed nations to improve their fiscal transparency, revenue performance, and resilience. This will go a long way to strengthen local financial systems. Novelty/Value: The study's nine research clusters and gaps—including the underrepresentation of African and Latin American studies and the development of digital and environmental fiscal themes—provide a clearer intellectual framework for the field than previous reviews.